2013
DOI: 10.3389/fonc.2013.00148
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Karyotypes: Survival of the Fittest

Abstract: Cancer cells are typically characterized by complex karyotypes including both structural and numerical changes, with aneuploidy being a ubiquitous feature. It is becoming increasingly evident that aneuploidy per se can cause chromosome mis-segregation, which explains the higher rates of chromosome gain/loss observed in aneuploid cancer cells compared to normal diploid cells, a phenotype termed chromosomal instability (CIN). CIN can be caused by various mechanisms and results in extensive karyotypic heterogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 125 publications
(168 reference statements)
1
67
2
Order By: Relevance
“…The authors argue that at “a certain time point when cells have acquired a chromosome composition that provides appropriate growth advantage in culture, maintenance of the chromosome composition becomes a selection force.” Evidence of genomic convergence was also found in the context of prostate cancer [52]. In [41], CIN and aneuploidy of cells have been studied. It was shown that once diploid cells become aneuploid, they also appear to become chromosomally stable, which provides a mechanism of instability reversal, see also [3].…”
Section: Discussionmentioning
confidence: 99%
“…The authors argue that at “a certain time point when cells have acquired a chromosome composition that provides appropriate growth advantage in culture, maintenance of the chromosome composition becomes a selection force.” Evidence of genomic convergence was also found in the context of prostate cancer [52]. In [41], CIN and aneuploidy of cells have been studied. It was shown that once diploid cells become aneuploid, they also appear to become chromosomally stable, which provides a mechanism of instability reversal, see also [3].…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, merotelic attachment is considered to be a major cause of CIN [47]. The incidence of lagging chromosomes in cancer cells exhibiting CIN is 10-60% [3]. Most lagging chromosomes eventually segregate properly, but sometimes they may be segregated to the wrong pole, giving rise to aneuploidy (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…1). Genetic heterogeneity resulting from CIN is supposedly followed by selective outgrowth of cells that have a growth advantage in a given (micro)environment [3]. Whole sequencing of cancer genomes revealed the tendency for oncogene-rich chromosomal regions to be amplified, and tumor suppressor gene-rich chromosomal regions lost [140].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…C hromosome instability (CIN), defined by an elevated rate of chromosome missegregation and breakage, results in diverse chromosome abnormalities in tumor cell populations (1)(2)(3)(4)(5)(6)(7). Accumulating cytogenetic analyses of more than 60,000 cases of human cancer have indicated that most of the solid tumors contain chromosome aberrations, with each tumor displaying a distinct abnormal karyotype (Mitelman database: cgap.nci.nih.gov/ Chromosomes/Mitelman).…”
mentioning
confidence: 99%